Implementasi Program Sekolah Berbasis Budaya di SMP Negeri 7 Yogyakarta - Herlina Damayanti; Sukiyanto Sukiyanto (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to describe the implementation of a culture-based school program at SMP Negeri 7 Yogyakarta. This study uses a qualitative phenomenological approach, with data collection techniques carried out through observation, interviews, and documentation. The results of the study show that the school has succeeded in integrating Javanese cultural values into various aspects of school life. Teachers have a good understanding of the concept of culture-based schools. Programs that have been implemented include cultural familiarization, extracurricular activities, and integration in learning. Although there are challenges, such as limited resources, financial support and the influence of globalization, students participation and support from teachers and parents are quite high. This study concludes that the culture-based school program at SMP Negeri 7 Yogyakarta has great potential in forming the character of students who have noble morals, creativity and have a strong identity. To increase the effectiveness of the program, the school is recommended to continue to develop more interesting programs, increase teachers capacity, strengthen collaboration with the community, and conduct regular evaluations.